Association of Functional Gastrointestinal Disorders with Adolescent Idiopathic Scoliosis - Soo-Bin Lee; Hyun-Wook Chae; Ji-Won Kwon; Sahyun Sung; Seong-Hwan Moon; Kyung-Soo Suk; Hak-Sun Kim; Si-Young Park; Byung Ho Lee (MDPI AG, 2024)
Numerous adolescents diagnosed with adolescent idiopathic scoliosis (AIS) often manifest symptoms indicative of functional gastrointestinal disorders (FGIDs). However, the precise connection between FGIDs and AIS remains unclear. The study involved adolescents drawn from sample datasets provided by the Korean Health Insurance Review and Assessment Service spanning from 2012 to 2016, with a median dataset size of 1,446,632 patients. The AIS group consisted of individuals aged 10 to 19 with diagnostic codes for AIS, while the control group consisted of those without AIS diagnostic codes. The median prevalence of FGIDs in adolescents with AIS from 2012 to 2016 was 24%. When accounting for confounding factors, the analysis revealed that adolescents with AIS were consistently more prone to experiencing FGIDs each year (2012: adjusted odds ratio (aOR), 1.21 [95% confidence interval (CI), 1.10-1.35], p < 0.001; 2013: aOR, 1.31 [95% CI, 1.18-1.46], p < 0.001; 2014: aOR, 1.24 [95% CI, 1.12-1.38], p < 0.001; 2015: aOR, 1.34 [95% CI, 1.21-1.49], p < 0.001; and 2016: aOR, 1.35 [95% CI, 1.21-1.50], p < 0.001). These findings suggest that AIS is correlated with an elevated likelihood of FGIDs, indicating that AIS may function as a potential risk factor for these gastrointestinal issues. Consequently, it is recommended to provide counseling to adolescents with AIS, alerting them to the heightened probability of experiencing chronic gastrointestinal symptoms.